PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN LAPTOP MEREK ACER (Studi Kasus pada Mahasiswa FISIP UNDIP Semarang) - Ahmad Yulizar; Apriatni Endang Prihatini (Universitas Diponegoro, 2017)
Laptop is a device that is very important because it helps every individual the usual deals to the technology of such students and college students to make it easier in carrying out almost every task .Acer always top ranked the top brand in an index on 2013-2015 year. However in three years the percentage of the acer decline every year though still be ranked first. This is caused by the increasing number of competitors who give a lower price and promotion that has intensively by a competitor. So as to make the community switch to using a competitor products.Type of this research is explanatory research, with a population of about 100 respondents who buy and use laptop brand acer. The sample collection to research it uses non-probablility sampling. Technique the sample collection use purposive sampling. Data collected through the questionnaire. The method of analysis the data used the use of tabulating cross, correlation, regression, regression simple, and multiple regression by using application SPSS.This study conclude that price and promotion influential of the decision the purchase, whether partial and a stimulant, variable promotion have more impact of variable price.Based on it, researchers suggest that company acer have to increase back promotion acer that consumers know that laptop acer is laptop numer one in Indonesia and also reevaluate them the prices offered has appropriate or not